Peran Tasawuf Dalam Membentuk Karakter Spiritual Masyarakat Muslim Di Kampung Agas Tanjung Uma Lubuk Baja Kota Batam - Sukri , Sukri (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
Sufism plays an essential role in shaping the spiritual character of Muslim communities, especially in the face of modernization and globalization, which tend to erode Islamic values. Kampung Agas, located in Tanjung Uma, Lubuk Baja, Batam City, is one of the areas that maintains the practice of Sufism in daily life. However, the community's understanding of Sufism varies, with many associating it only with dhikr and wirid practices without comprehending its essence in self-purification and moral development. This study employs a qualitative approach using field studies and in-depth interviews with religious leaders, community members, and taklim assembly administrators in Kampung Agas. Participatory observation was also conducted to understand the practical application of Sufism in daily life. The findings indicate that Sufism contributes to shaping the community's spiritual character by enhancing religious awareness, controlling desires, and strengthening social values such as honesty, patience, and compassion. However, challenges remain in spreading a broader understanding of Sufism, particularly among the younger generation, who are more influenced by materialism and individualism. In conclusion, Sufism has a positive impact on the spiritual development of the Kampung Agas community. However, innovative approaches in religious outreach are needed to make it more relevant to contemporary developments, such as utilizing digital media and incorporating Sufi-based education in schools